2015
DOI: 10.1159/000444920
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus EBNA-2 Polymorphic Patterns in Nasopharyngeal Carcinoma in Southern China

Abstract: Objectives: The aim of this study was to characterize the specific Epstein-Barr virus (EBV) polymorphisms from nasopharyngeal carcinoma (NPC) patients and healthy donors in Southern China, and to explore the relationship between EBV genotypes and NPC. Methods: The EBNA-2 gene of 32 EBV-positive NPCs and 39 EBV-positive throat washing (TW) samples from healthy individuals from Southern China was analyzed using PCR and sequencing. Results: We found E2-A to be the predominant subtype in Southern China. The distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(35 reference statements)
1
0
0
Order By: Relevance
“…The second pastern of group 2, which was represented by T69, carried 11 amino acid changes at residue 151 (ATT:Ile → ATG:Met), 163 (ACG:Arg → GTG:Val), 185 (CAA:Gln → CGA:Arg), 195 (ATG:Met → ACG:Thr), 245 (CCA:Pro → CAA:Gln), 246 (CGC:Arg → CGT:Ser), 280 (ACT:Thr → AAT: Asn), 476 (GAG:Glu → GGG:Gly), 468 (ATC:Ile → ACC:Thr), 490 (CCC:Pro → ACC:Thr), 509 (AAC:Asn → GAC:Asp) and one insertion in 241 (CTC: Leu). In the current study, the variants E2-A was identified as the predominant subtype in our samples, which was also characterized as the frequent subtype in other Asian countries, including Hong Kong (Kwok et al, 2014), Southern China (Wu et al, 2015).…”
Section: Sequence Variation Data Of Ebna-2 In Npc Biopsy Samplessupporting
confidence: 64%
“…The second pastern of group 2, which was represented by T69, carried 11 amino acid changes at residue 151 (ATT:Ile → ATG:Met), 163 (ACG:Arg → GTG:Val), 185 (CAA:Gln → CGA:Arg), 195 (ATG:Met → ACG:Thr), 245 (CCA:Pro → CAA:Gln), 246 (CGC:Arg → CGT:Ser), 280 (ACT:Thr → AAT: Asn), 476 (GAG:Glu → GGG:Gly), 468 (ATC:Ile → ACC:Thr), 490 (CCC:Pro → ACC:Thr), 509 (AAC:Asn → GAC:Asp) and one insertion in 241 (CTC: Leu). In the current study, the variants E2-A was identified as the predominant subtype in our samples, which was also characterized as the frequent subtype in other Asian countries, including Hong Kong (Kwok et al, 2014), Southern China (Wu et al, 2015).…”
Section: Sequence Variation Data Of Ebna-2 In Npc Biopsy Samplessupporting
confidence: 64%